Almost global stability of nonlinear switched systems with mode-dependent and edge-dependent average dwell time. (August 2021) - Kıvılcım, Ayşegül; Karabacak, Özkan; Wisniewski, Rafael
Abstract: It has recently been shown that almost global stability of nonlinear switched systems can be characterized using multiple Lyapunov densities. This has been accomplished for switched systems subject to a minimum dwell time or an average dwell time constraint. In this paper, as an extension of the aforementioned results, we provide a sufficient condition on mode-dependent and edge-dependent average dwell time to ensure almost global stability of a nonlinear switched system. The relations between average dwell time, mode-dependent, and edge-dependent average dwell time have been discussed. The obtained results for nonlinear switched systems imply the existing results for linear switched systems.